Placental Nkx2-5 and target gene expression in early-onset and severe preeclampsia. (November 2014) - Rivers, Elena R.; Horton, Anthony J.; Hawk, Angela F.; Favre, Elizabeth G.; Senf, Katherine M.; Nietert, Paul J.; Chang, Eugene Y.; Foley, Ann C.; Robinson, Christopher J.; Lee, Kyu-Ho
<x xml:space="preserve">Abstract</x> Objective: Preeclampsia (PE) affects 2–8% of pregnancies worldwide and is a significant source of maternal and neonatal morbidity and mortality. However, the mechanisms underlying PE are poorly understood and major questions regarding etiology and risk factors remain to be addressed. Our objective was to examine whether abnormal expression of the cardiovascular developmental transcription factor, Nkx2-5, was associated with early onset and severe preeclampsia (EOSPE). Methods: Using qPCR and immunohistochemical assay, we examined expression of Nkx2-5 and target gene expression in EOSPE and control placental tissue. We tested resulting mechanistic hypotheses in cultured cells using shRNA knockdown, qPCR, and western blot. Results: Nkx2-5 is highly expressed in racially disparate fashion (Caucasians > African Americans) in a subset of early EOSPE placentae. Nkx2-5 mRNA expression is highly correlated (Caucasians > African Americans) to mRNA expression of the preeclampsia marker sFlt-1, and of the Nkx2-5 target and RNA splicing factor, Sam68. Knockdown of Sam68 expression in cultured cells significantly impacts sFlt-1 mRNA isoform generation in vitro, supporting a mechanistic hypothesis that Nkx2-5 impacts EOSPE severity in a subset of patients via upregulation of Sam68 to increase sFlt-1 expression. Expression of additional Nkx2-5 targets potentially regulating metabolic stress response is also elevated in a racially disparate fashion in EOSPE. Conclusions: Expression of Nkx2-5 and its target genes may directly influence the genesis and racially disparate severity, and define a mechanistically distinct subclass of EOSPE.